2010
DOI: 10.1136/vr.b4842
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary students’ understanding of a career in practice

Abstract: Lack of a clear perception of the realities of a career in veterinary medicine could adversely affect young graduates' satisfaction with the profession and their long-term commitment to it. Veterinary students' understanding of a career in practice were explored. Traditional-entry first-year and final-year students, as well as entry-level 'Gateway' (widening participation) students, were invited to complete a questionnaire exploring their pre-university experiences and their understandings of a career in gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
(46 reference statements)
3
23
1
Order By: Relevance
“…In practice, it has frequently been reported that vets experience considerable stress (RCVS, 2014:16), doubts, anxieties, insecurities, mental health problems, drug addiction and high levels of suicide (Bartram and Baldwin, 2010;Platt et al, 2012). Nevertheless, there is limited understanding of how insecurities and concerns might partly reflect veterinary colleges not preparing students adequately for "a career in practice", especially relating to fears about making mistakes and issues of self-confidence (Tomlin et al 2010). For example, in their first year of practice 78% of graduates admitted to making 'iatrogenic' 4 mistakes due to inexperience, time pressures and lack of supervision and some 'suffered a loss of confidence…felt guilty or upset…and questioned whether they should continue to work as a veterinarian' (Mellanby and Herrtage 2004:762).…”
Section: Vets In Practicementioning
confidence: 99%
“…In practice, it has frequently been reported that vets experience considerable stress (RCVS, 2014:16), doubts, anxieties, insecurities, mental health problems, drug addiction and high levels of suicide (Bartram and Baldwin, 2010;Platt et al, 2012). Nevertheless, there is limited understanding of how insecurities and concerns might partly reflect veterinary colleges not preparing students adequately for "a career in practice", especially relating to fears about making mistakes and issues of self-confidence (Tomlin et al 2010). For example, in their first year of practice 78% of graduates admitted to making 'iatrogenic' 4 mistakes due to inexperience, time pressures and lack of supervision and some 'suffered a loss of confidence…felt guilty or upset…and questioned whether they should continue to work as a veterinarian' (Mellanby and Herrtage 2004:762).…”
Section: Vets In Practicementioning
confidence: 99%
“…There is considerable anxiety about the ‘lack of time to do a proper job’, which may lead to mistakes (Mellanby and Herrtage 2004, Tomlin and others 2010), and pattern recognition being an inappropriate way to approach diagnosis and therapy (Tomlin and others 2008). Such students fail to acknowledge the supreme skill of many experienced primary health care veterinarians, and the robustness of their systems in delivering effective and affordable health care.…”
Section: Implications For Veterinary Educationmentioning
confidence: 99%
“…Although the causes of this are multifactorial, finances appear to be a pivotal factor, with suggestions that lack of pay rises and low pay rates are the greatest cause of dissatisfaction among veterinarians. 6,7 Veterinarians are four times more likely to commit suicide than the general population and twice as likely as other high-risk health professionals, such as doctors and dentists. 8 Onethird of medical general practitioners committing suicide have financial difficulties and the statistics are likely to be similar within the veterinary profession.…”
Section: How We Make Ends Meeteconomic Sustainability Of the Veterinamentioning
confidence: 99%
“…4,5,9 In one study, 92.4% of pre-veterinary and veterinary students wanted to work in general practice on graduation. 6 The stress of the pay rates and on-call hours are not recognised until after commencement of employment when some may consider nonpractice careers. 6 By this stage there is a competitive disadvantage in the job market for non-practice positions because knowledge is out-of-date and graduate training programs are no longer possible in these other areas.…”
Section: How We Make Ends Meeteconomic Sustainability Of the Veterinamentioning
confidence: 99%
See 1 more Smart Citation